Implementation of Video-Based Hypermedia Learning in Science Material for Grade III Elementary Schools - tripujiyuliani02; Riza Apriliniawati; Tri Puji Yuliani (Universitas PGRI Semarang, 2025)
This study aims to explain the implementation of the use of hypermedia media based on learning videos for Natural and Social Sciences (IPAS) material among third-grade students of SD Negeri Deles 01. The method used in this study is a descriptive qualitative approach with a total of 18 students and one teacher as subjects. Data were obtained through observation, interviews, and documentation activities, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings of this study indicate that the use of interactive videos in IPAS learning can increase student participation, facilitate understanding of abstract concepts such as the water cycle, and create a joyful learning atmosphere. Students appeared active in asking questions, providing answers, and were able to re-explain the material they had watched after watching the video. Teachers felt the benefits of this media because it allows for efficient and attention-grabbing delivery of material. Therefore, the use of video-based hypermedia media is considered effective for implementation in IPAS learning at the elementary school level as an effort to realize contextual, visual-based learning, and in accordance with the stage of students' cognitive development.